Effects of materialism on problematic smartphone dependency among adolescents: The role of gender and gratifications. (October 2020) - Gentina, Elodie; Rowe, Frantz
Highlights: Paper argues for the concept of Problematic Smartphone Dependency (PSD). Model explains PSD by materialism mediated by use gratifications at adolescence. Model is consistent with I-PACE model, gratification theory and social role theory. Both social-oriented and process-oriented smartphone use are influenced by gender. Gender moderates the relationship between materialism and PSD for teenagers. Abstract: We study youth materialism as an antecedent of problematic smartphone dependency among adolescents. Based on Uses and Gratifications theory and the I-PACE framework, we consider process- and social-oriented smartphones as mediators in the relationship between youth materialism and problematic smartphone dependency. Using data from 463 French late adolescents (mean 16.8 years; 58 % female), known as digital natives, we demonstrate that paths differ depending on gender. For girls, youth materialism is positively related to problematic smartphone dependency via social-oriented smartphone use, whereas this relationship is nonsignificant for boys. Moreover, youth materialism is positively related to problematic smartphone dependency via process-oriented smartphone use for both boys and girls, but the relationship is stronger for boys than for girls. We discuss the implications of these results for business and social policies.